The Public Versus Private Space: The Feminization of Work in Tea Plantation. Issue 2 (December 2018) - Baruah, Juri
In many parts of the world, plantation labour is one of the lowest paid work categories in which women are highly marginalized. The Sivasagar district of Assam is predominated by tea gardens. Historically, this district has always had tea gardens and tea garden companies. This article highlights the idea of 'feminization of work' by differentiating the public/private spaces based on the dichotomy of 'open/closed' space in tea bagans (tea gardens) in the district, and focuses on the division of permanent and faltu (temporary) labourers and how women are trapped in these dichotomies. The article carries the narratives of women labourers from two tea gardens, which will be referred to as Tea Garden A and Tea Garden B, in the district, collected through interviews.